The Model of Manufacturing Industries Employee Performance - Raharjo, Dwi Sihono; Sulistiasih, Sulistiasih (International Review of Management and Marketing, 2019)
The purpose of this study is to know the influence of leadership style, organizational commitment and motivation on employee performance at Manufacturing Industries DKI Jakarta. The methods of this research are descriptive and explanatory survey with sample size is 450 employee, methode analysis in this research is path analysis. The research finding is leadership style, organizational commitment, and work motivation simultaneously have positive and significant effect on employee performance at Manufacturing Industries in DKI Jakarta, and motivation have dominant effcet on employee performance. Keywords: Leadership Style, Organizational Commitment, Motivation, and Employee Performance. JEL Classifications: M12, M54, N75 DOI: https://doi.org/10.32479/irmm.8594